1998
DOI: 10.1017/s1138741600005369
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Sensitivity Function of the Albino Rat Determined Electrophysiologically

Abstract: Albinism alters the neural projections of the visual system. The authors wondered how this would affect visual fúncrion in rodents. They had previously shown that it doesn't aher the luminance threshold. Tbey now explore visual aduity in the albino rat. In this work, they describe its contrast sensitivity funclion (CSF), as determined electrophysiologically. They recorded cortical visual evoked posentials (VEP) on six albino rats, stimulated by sinusoidal consrast reversal gratings. The curve showed the sanie … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(47 reference statements)
1
2
0
2
Order By: Relevance
“…They found lower contrast sensitivity at all spatial frequencies compared with those obtained by Silveira et al (1987) in the pigmented rat, and visual acuity was 0.48 cpd. Despite the methodological differences, a remarkable similarity was found between the results obtained by Birch and Jacobs (1979) and the results obtained by Silveira et al (1987) and Tejada and Tedó (1998). Prusky, West, & Douglas (2000) compared the visual acuity of rats and mice and found that rats had two-fold higher visual acuity than mice.…”
Section: Luminance Spatial Contrast Sensitivity Of Mammalssupporting
confidence: 58%
See 2 more Smart Citations
“…They found lower contrast sensitivity at all spatial frequencies compared with those obtained by Silveira et al (1987) in the pigmented rat, and visual acuity was 0.48 cpd. Despite the methodological differences, a remarkable similarity was found between the results obtained by Birch and Jacobs (1979) and the results obtained by Silveira et al (1987) and Tejada and Tedó (1998). Prusky, West, & Douglas (2000) compared the visual acuity of rats and mice and found that rats had two-fold higher visual acuity than mice.…”
Section: Luminance Spatial Contrast Sensitivity Of Mammalssupporting
confidence: 58%
“…Silveira et al (1987) found that the CSF of pigmented rats was band-pass, peaking at 0.1 cpd with a visual acuity of 1.2 cpd. Tejada and Tedó (1998) used an approach similar to Silveira et al (1987) but used albino rats. They found lower contrast sensitivity at all spatial frequencies compared with those obtained by Silveira et al (1987) in the pigmented rat, and visual acuity was 0.48 cpd.…”
Section: Luminance Spatial Contrast Sensitivity Of Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…De um lado, há um estímulo cinza-homogêneo (estímulo neutro), enquanto que do outro lado, há uma grade linear vertical ou concêntrica (estímulo teste) com uma das 10 frequências espaciais, de 0,15 a 0,60 cpg, calibradas para serem vistas a 27 cm (distância do olho do rato ao centro do estímulo, no momento da escolha forçada), escolhidas de acordo com estudos que mostram que a acuidade visual cartesiana de ratos albinos Wistar se encontra nesta faixa (Keller et al, 2000;Prusky et al, 2002;Tejada & Tedó, 1998).…”
Section: O Labirinto De Imagens Foi Desenvolvido Em Parceria Com a Inunclassified
“…Nessa primeira sessão, o objetivo era fazer o animal distinguir o estímulo teste, um círculo com uma frequência espacial (que estava associado ao reforço), de um círculo totalmente cinza -estímulo neutro. A frequência espacial de teste utilizada durante todo o condicionamento foi de 0,15 ciclos por grau de ângulo visual (cpg), uma frequência de fácil detecção por ratos (Keller et al, 2000;Prusky et al, 2002;Tejada & Tedó, 1998).…”
Section: -Protocolo De Análise Comportamentalunclassified